Identification of Potential Biomarkers in Association With Progression and Prognosis in Epithelial Ovarian Cancer by Integrated Bioinformatics Analysis - Liu, Jinhui; Meng, Huangyang; Li, Siyue; Shen, Yujie; Wang, Hui; Shan, Wu; Qiu, Jiangnan; Zhang, Jie; Cheng, Wenjun (Frontiers in Genetics, 2019)
Epithelial Ovarian Cancer (EOC) is one of the malignancies in women, which has the highest mortality. However, the micro level mechanism has not been discussed in detail. The expression profiles GSE27651, GSE38666, GSE40595, and GSE66957 including 188 tumor and 52 nontumor samples were downloaded from the Gene Expression Omnibus (GEO) database. The differentially expressed genes (DEGs) were filtered using R software and we performed functional analysis using the Clusterprofiler. Cytoscape software, the molecular complex detection (MCODE) plugin and database STRING analyzed DEGs to construct protein-protein interaction (PPI) network. We identified 116 DEGs including 81 upregulated and 35 downregulated DEGs. Functional analysis revealed that they were significantly enriched in extracellular region and Biosynthesis of amino acids. We next identified 4 bioactive compounds (vorinostat, LY-294002 ，trichostatin A and tanespimycin) based on CMap. Then 114 nodes were obtained in PPI. The three most relevant modules were detected. In addition, according to degree≥10, 14 core genes including FOXM1, CXCR4, KPNA2, NANOG, UBE2C, KIF11, ZWINT, CDCA5, DLGAP5 ,KIF15, MCM2, MELK, SPP1 and TRIP13 were identified. Kaplan‐Meier analysis, Oncomine and GEPIA showed that overexpression of FOXM1, SPP1, UBE2C, KIF11, ZWINT, CDCA5, UBE2C and KIF15 were related to bad prognosis of EOC patients. CDCA5, FOXM1, KIF15, MCM2 and ZWINT were associated with stage. Receiver operating characteristic (ROC) curve showed that mRNA levels of these 5 genes exhibited better diagnostic efficiency for normal and tumor tissues. The Human Protein Atlas database (HPA) was performed. The protein levels of these 5 genes were significantly higher in tumor tissues compared with normal tissues. Functional enrichment analysis suggested that all the hub genes played crucial roles in citrate cycle tca cycle. Furthermore，the univariate and multivariate Cox proportional hazards regression showed that ZWINT was independent prognostic indictor among EOC patients. The genes and pathways discovered in the above studies may open a new direction for EOC treatment.